The prophet yusuf and the king's dream - Khan, Saniyasnain (Goodword Books New Delhi, 2010)
The Prophet Yusuf and the King's Dream is a captivating tale that recounts the story of Prophet Yusuf, showcasing his gift of interpretation, resilience through adversity, and the importance of faith as he navigates challenges and fulfills his destiny in ancient Egypt.